Effects of psoriasis on the quality of life of patients: an integrative literature review (Research, Society and Development, 2022)
Objective: The present study aims to explain the effects that psoriasis affects on the quality of life of patients. Methods: The method used is an Integrative Literature Review, with the purpose of gathering and synthesizing research results on a delimited topic, carried out with 8 articles collected in the database,which are Scientific Electronic Library Online ( SciELO), Virtual Health Library (BVS), Latin American and Caribbean Literature on Health Sciences (Lilacs), Portal of Electronic Journals in Psychology (PePSIC). Results: With the results developed, it was possible to observe that psoriasis has a negative impact on the quality of life of individuals, this is due to the stigmatization that still exists about the disease, and how the affected individual feels as a result of it. Conclusion: It is concluded that individuals with psoriasis have a direct impact on quality of life, given that it does not affect only the biological, but the physical, psychological and social.